"Dangling Carrots Before Marxists": U.S.-Mozambican Relations Since 1981 - Nash, Philip (Tufts Archival Research Center, 2005)
Volume 11, Issue 2. Summer One of the more controversial developments in recent U.S. foreign policy is the adoption of the "Reagan Doctrine," a policy that includes support for guerrilla movements opposed to Soviet-backed states in Central America, Asia, and Africa. Yet in an apparent reversal of its own doctrine, the Reagan administration has sought closer relations with the avowedly Marxist-Leninist government of Mozambique. Philip Nash examines the origins and development of this relationship from both the American and Mozambican viewpoints, and introduces a more general question: how can a government, while seeking to enlist support for the broad themes of its foreign policy, retain the flexibility to deal with local issues in a way that, on the surface, runs counter to those themes?